Fiscal Transparency and Economic Outcomes. (IMF Working Papers; Working Paper ;, 2005)
This paper develops indices of fiscal transparency for a broad range of countries based on the IMF's Code of Good Practices on Fiscal Transparency, using data derived from published fiscal transparency modules of the Reports on the Observance of Standards and Codes (ROSCs). The indices covers four clusters of fiscal transparency practices: data assurances, medium-term budgeting, budget execution reporting, and fiscal risk disclosures. More transparent countries are shown to have better credit ratings, better fiscal discipline, and less corruption, after controlling for other socioeconomic variables.